Further sesquiterpene pyridine alkaloids from Maytenus aquifolium - Corsino, Joaquim [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Pereira, Ana Maria S.; França, Suzelei Castro; Furlan, Maysa [UNESP] (Elsevier, 1998)
Two new sesquiterpene evoninate alkaloids, aquifoliunine E-III and aquifoliunine E-IV, were isolated from the root bark of Maytenus aquifolium. The structures of the new compounds were elucidated on the basis of spectroscopic methods, including ES-MS.
Keywords: Celastraceae; Maytenus aquifolium; Root bark; Sesquiterpene evoninate alkaloids; aquifoliunine e iii; aquifoliunine e iv; sesquiterpene derivative; unclassified drug; drug isolation; drug structure; mass spectrometry; nonhuman; nuclear magnetic resonance spectroscopy; plant root; stereochemistry